دَورُ الإدارة المَدرسيَّة في تنميَةِ قيَم المُواطَنة لدَى طلبَة التَّعليم مَا بعْدَ الأسَاسي بسلطنَةِ عُمَان - Ahmed Sulaiman Albrashdi, T.; Awang Mat Dahan, H.B. (Universiti Sains Islam Malaysia, 2024)
This quantitative study aimed to investigate teachers' administrative empowerment and its relationship with their job satisfaction in post-basic schools in the governorate of North Batinah in the Sultanate of Oman. The study used a descriptive method to collect the necessary data for the current study. To achieve the purpose of the study a stratified sampling method was used to choose the respondents. The questionnaire consisted of 54 items was distributed to 300 participants. The findings revealed that: Administrative empowerment and job satisfaction of the participating received high mean scores. In the authority dimension of the administrative empowerment, a statistically significant difference between males and females where male participants indicated higher perceptions at p≤0.05. There was a statistically significant difference between male and female participants in the social status dimension, where female participants showed higher satisfaction at p≤0.05. There was a statistically high significant relationship (p≤0.01) between the administrative empowerment and job satisfaction for teachers. This relationship indicates when teachers' administrative empowerment increases; job satisfaction for teachers also proportionally increases. The researcher recommended; Educational institutions need to adopt educational policies that call for power-sharing and allow a big number of staff to participate in decision-making.